Growing disease-free organic tomato - Singh, Ramesh K.; Chaubey, T; Rai, N; Singh, B (Indian Horticulture, 2019)
Many of the conventional pesticides and fertilizers persist in the soil are harmful to the beneficial soil microorganism including earthworms, thereby resulting in degradation of soil fertility, increasing environmental awareness, pollution potential and health hazards. In such a situation, agriculture is shifting from chemical to organic farming, as well as demand for organic vegetable production is also increasing day by day. Among vegetables cultivation of resistant tomato (free from diseases and pests) by organic farming has a challenge for tomato growers. Organic farming is a system that seeks to avoid the use of chemical, fertilizers and pesticides. Tomato cultivated by organic farming produces healthy, nutritious and residual free fruits. Organic tomatoes are always in high demand in both local and whole-sale markets and have been need of farmers for their easy cost production and consumers for their good health.